An Improved Method for Accurate Phenotyping of Corn Stalk Strength. Issue 5 (1st September 2014) - Robertson, Daniel; Smith, Simeon; Gardunia, Brian; Cook, Douglas
ABSTRACT: Weak stems or stalks in grass crop species increase the likelihood of stalk failure, thereby reducing yield. Three‐point bending tests are often employed in selective breeding studies to characterize stalk strength. However, it is hypothesized that the loading setup used during three‐point bending experiments may significantly alter test results. To investigate this hypothesis, two different loading configurations were employed in conducting three‐point bending experiments of corn (Zea mays L.) stalks. In the first configuration, stalks were loaded and supported at nodes. In the second configuration, stalks were loaded and supported at internodal segments. Significantly higher bending moments were experienced at internodal segments during the node‐loaded configuration than was required to fail the same segment during internode‐loaded tests. This is because the loading anvil significantly deforms the stalk's cross section when it is placed on an internodal segment, thereby inducing premature failure. In addition, internode‐loaded tests were observed to produce unnatural failure patterns, while node‐loaded tests demonstrated natural variability in failure location. While transverse deformation of the stalk cross section cannot be eliminated in three‐point bending tests, its effects can be mitigated by placing the loading anvil at nodal locations, which are much stiffer than internode regions. Maximizing the span length of bending tests likewise reduces transverse deformation of stalk cross sections. These results are relevant to selective breeding studies designed to produce lodging resistant crop hybrids.